FDI and Labor: A Dynamic Duo for Vietnam’s Provincial Exports - Nguyen, Thi Thanh; Nguyen, Thi Tinh (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2025)
This study investigates the interconnected roles of foreign direct investment (FDI) and labor in driving provincial export performance in Vietnam. Employing the Feasible Generalized Least Squares method and secondary data covering 63 provinces from 2017 to 2022, the research reveals a nuanced relationship between FDI and labor indicators. The result indicates that FDI, skilled labor, and labor size individually boost exports. Furthermore, the impact of FDI on exports might be amplified when combined with a skilled labor force; however, the interaction between FDI and labor size may negatively impact provincial exports due to resource constraints and skill mismatches. These findings underscore the importance of strategic FDI policies and investments in human capital development to foster sustainable and competitive provincial export growth in Vietnam.